CASE STUDY: THE INFLUENCE OF FAMILY ENVIRONMENT ON STUDENTS' MISBEHAVIOR IN MADRASAH ALIYAH NEGERI 4 KEDIRI - dewi, fatqu (English Teaching Journal and Research: Journal of English Education, Literature, And Linguistics, 2025)
This study aims to investigate how family pressure affects students' delinquent behavior at school. The subject of the study consisted of a student who exhibited such delinquent behavior. The findings obtained from this study indicate that family pressure has a significant impact on students' delinquent behavior. Therefore, the results of this study show how important the role of parents and families is in helping to overcome students' delinquent behavior at MAN 4 KEDIRI school. Home is the first and foremost environment that shapes a child's character and attitude. This study also focuses on analyzing the influence of the family environment on the development of children's personality, by paying attention to the interaction between parents and children and parenting patterns at home which are considered important in the growth of children's character and personality. The method used by this study is a qualitative method with a literature study approach. From the results of the study, it was found that the quality of the family environment is closely related to the good character of the child. This study aims to analyze how teachers try to solve family environmental problems that have an impact on students' learning motivation.